PENINGKATAN KAPASITAS MASYARAKAT TRADISIONAL DALAM MENGGUNAKAN PERILAKU SATWALIAR SEBAGAI INDIKATOR PHENOMENA ALAM - Wajo, Alhidayat; Badaruddin, Ernywati; Kaya, Manuel; Kaya, Ivonne R. G. (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2023)
Indigenous peoples who have lived in the Maluku Islands since their ancestors have applied various forms of local wisdom to the conservation of natural resources and the environment around them. As coastal communities who live on small islands separated by the sea, there are various limitations, especially communication and transportation which are determined by the season. The community seeks to know the dynamics of natural changes through various life experiences known as NANAKU. The layout of the island greatly determines the application of a local wisdom, so that what is done by the people in the Southeast Maluku Regency is different from on the islands of Seram or Buru Island. The wildlife on Seram Island and Buru Island are different from the endemic wildlife on the Aru Islands. The problems faced by small island communities are transportation, communication of science and technology. Wildlife as God's creation must be guarded and protected from extinction because it has important benefits for our lives. Wildlife can be used as an indicator (Nanaku) to find out natural phenomena around us. The role of foresters and ecotourists in motivating rural communities is needed so that environmental components, especially wildlife, can be put to good use.